Thermo-mechanical fatigue crack growth behaviour of Ti-6246 - JENNIE PALMER (2021)
Within the gas turbine engine, the high transient thermal stresses developed due to variations in power requirements during a typical flight cycle give rise to the phenomenon of thermo-mechanical fatigue (TMF). Associated with higher operating temperatures, the study of TMF within the gas turbine engine has mainly been focused on materials used in the latter turbine sections. However, the increasing temperatures to improve operating efficiency have led to the requirements for an understanding of the TMF behaviour in materials used for the later stages of the compressor. As such, fatigue crack growth rates are required to be evaluated under non-isothermal conditions along with the development of a detailed understanding of related failure mechanisms. In the current study a bespoke TMF crack growth (TMFCG) test set up has been developed and validated to investigate the TMFCG behaviour of the titanium alloy, Ti-6246. The study has explored the effects of phasing between mechanical loading and temperature, as well as the effects of maximum cycle temperature. Results show in-phase (IP) test conditions to have faster crack growth rates than out-of-phase (OP) test conditions, due to increased temperature at peak stress and therefore increased time-dependent crack growth. Fractography evidences subtle differences in fracture mechanisms and the microstructural analysis along the crack path has aided the characterisation of damage mechanisms in IP and OP test conditions.